(untitled) (Experimental biology, 2015)
Developed based on the original Kazakh strains of PCR test-system can be used in practice for Veterinary Virology and epizootiology for differential diagnosis of outbreaks of influenza A and Newcastle disease in populations of wild and domestic birds.